2021
DOI: 10.46799/jhs.v2i9.274
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Hasil Pemeriksaan HBSAG pada Pendonor di Unit Donor Darah Palang Merah Indonesia Kabupaten Kudus

Abstract: Hepatitis B merupakan salah satu penyakit infeksi yang menyerang hati dapat bersifat akut dan kronik. Transfusi darah merupakan salah satu jalur penularan VHB secara horizontal yang sering terjadi. Pada pendonor yang menderita penyakit hepatitis B atau menjadi karier hepatitits B, maka darah yang mengandung virus hepatitis B tersebut dapat ditularkan kepada resipien melalui transfusi darah. Beberapa tindakan yang dilakukan untuk mencegah penularan hepatitis yaitu dengan adanya pemeriksaan HBsAg. Apabila HBsAg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
0
0
1
Order By: Relevance
“…19 Another study conducted by Lestari &Saputro on Kudus City in 2020 also shown a similar result with this study. 20 These report also linear with the report of health minister of Indonesia that found the prevalence of syphilis cases from 2007 until 2016 was run into upward every year from 0,38% in 2007 to 0,77% in 2016. 17 From this increasing percentage of cases and report in Indonesia, it can be interpreted that cases of transmission of syphilis through blood transfusions are very serious matters and special treatment is needed to reduce transmission, especially through blood transfusions.…”
Section: Discussionsupporting
confidence: 55%
“…19 Another study conducted by Lestari &Saputro on Kudus City in 2020 also shown a similar result with this study. 20 These report also linear with the report of health minister of Indonesia that found the prevalence of syphilis cases from 2007 until 2016 was run into upward every year from 0,38% in 2007 to 0,77% in 2016. 17 From this increasing percentage of cases and report in Indonesia, it can be interpreted that cases of transmission of syphilis through blood transfusions are very serious matters and special treatment is needed to reduce transmission, especially through blood transfusions.…”
Section: Discussionsupporting
confidence: 55%
“…Menurut data WHO prevalensi hepatitis virus C di Indonesia berkisar 1-2,4% Prevalensi penyakit yang ada di masyarakat, keberhasilan skrining yang digunakan, kekebalan tubuh penerima dan jumlah donor tiap unit darah merupakan faktor lain dari penularan penyakit infeksi melalui tranfusi darah. Karena dampak infeksi virus yang bisa menyebabkan penularan infeksi melalui transfusi darah maka pengujian skrining sangat penting untuk menghindari penyakit menular seperti HCV, HbsAg, HIV dan sifilis (Febri, 2019). Menurut Kemenkes RI (2013), penularan infeksi adalah perpindahan agen infeksi dari sumber infeksi ke penjamu yang rentan, sehingga menimbulkan infeksi.…”
Section: Pendahuluanunclassified